(untitled) (Journal of actual problems of jurisprudence, 2018)
The article examines the legal nature of the presumption of innocence as a fundamental guideline and start the criminal process of the Republic of Kazakhstan. Actualized need for further improvement of legislation defining the legal regime of the presumption of innocence in criminal proceedings. The questions of the impact of the presumption of innocence on various aspects of criminal procedure of proof in terms of adversarial criminal proceedings. Key words: presumption of innocence, the criminal process, the properties of evidence, proof, judicial investigation.